Understanding healthcare innovation systems: the Stockholm region case. Issue 8 (21st November 2016) - Larisch, Lisa-Marie; Amer-Wåhlin, Isis; Hidefjäll, Patrik
Abstract : Purpose: There is an increasing interest in understanding how innovation processes can address current challenges in healthcare. The purpose of this paper is to analyze the wider socio-economic context and conditions for such innovation processes in the Stockholm region, using the functional dynamics approach to innovation systems (ISs). Design/methodology/approach: The analysis is based on triangulation using data from 16 in-depth interviews, two workshops, and additional documents. Using the functional dynamics approach, critical structural and functional components of the healthcare IS were analyzed. Findings: The analysis revealed several mechanisms blocking innovation processes such as fragmentation, lack of clear leadership, as well as insufficient involvement of patients and healthcare professionals. Furthermore, innovation is expected to occur linearly as a result of research. Restrictive rules for collaboration with industry, reimbursement, and procurement mechanisms limit entrepreneurial experimentation, commercialization, and spread of innovations. Research limitations/implications: In this study, the authors analyzed how certain functions of the functional dynamics approach to ISs related to each other. The authors grouped knowledge creation, resource mobilization, and legitimacy as they jointly constitute conditions for needs articulation and entrepreneurial experimentation. The economic effects of entrepreneurial experimentation and needs articulation are mainly determined by the stage of market formation and existence of positive externalities. Social implications: Stronger user involvement; a joint innovation strategy for healthcare, academia, and industry; and institutional reform are necessary to remove blocking mechanisms that today prevent innovation from occurring. Originality/value: This study is the first to provide an analysis of the system of innovation in healthcare using a functional dynamics approach, which has evolved as a tool for public policy making. A better understanding of ISs in general, and in healthcare in particular, may provide the basis for designing and evaluating innovation policy.